Activity approach in developing the technology of author's projective cards "Heroes and Villains" - Anastasia Kuntsevskaya (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article devoted to the technology of Structure-Role Projective Cards "Heroes and Villains", which has been developed according to the Theory of Activity methodology. Author provides methodological analysis of the Theory and analyses the issue of using metaphor in psychother- apy. Structure-Role Projective Cards "Heroes and Villains" are presenting 54 images with defined meanings in accordance with the basic structures of activity: the position, actions, target and potentially conflictual situations.
Keywords: activity-oriented approach; projective cards; metaphor